Sensitivity analysis of a triangulation network - Ortiz Sánchez, Oswaldo (2000)
Through probabilistic analysis may prove the truth or falsity of a hypothesis. The application of the 3 basic laws of probability theory can prove the certainty of the location of points of a network of triangulation surveying several adjacent mining concessions whose location accuracy was questioned by one of the parties. The names of the vertices of the triangles are true and were taken to demonstrate the method.